Characterization of nonmotile variants of Escherichia coli O157 and other serotypes by using an antiflagellin monoclonal antibody. - Feng, P (1996)
An antiflagellin monoclonal antibody (15D8) was used to detect the presence of flagella in nonmotile variants of several pathogenic Escherichia coli serotypes. Of the 48 isolates examined, 15 reacted with monoclonal antibody 15D8 and were culturally confirmed to be motile. Of the 38 clinical strains designated O157:NM or O157:H-, 7 were antibody reactive and motile and agglutinated with anti-H7 sera.